Influence of Environmental Factors in the Development and Outcomes of Inflammatory Bowel Disease - Vedamurthy, Amar (Gastroenterol Hepatol (N Y), 2019)
Inflammatory bowel disease (IBD), which mainly comprises Crohn’s disease (CD) and ulcerative colitis (UC), is a term for chronic inflammatory diseases of the gut arising due to a dysregulated immune response to a dysbiotic gut microbiome on a background of genetic predisposition. However, genetics explains a small fraction of risk, and the external environment plays a large and important role in disease pathogenesis and natural history. Cigarette smoking, one of the earliest- and most-studied risk factors, increases the risk of CD onset and is associated with severe disease. In contrast, although smoking cessation increases the risk of UC onset and relapse, current smoking appears to be protective. Appendectomy is inversely associated with the risk of UC. Various dietary factors may influence risk of IBD, including an inverse association with dietary fiber. Exclusion diets have anecdotal reports of efficacy but lack evidence from rigorous clinical trials. Psychosocial factors such as depression, stress, and sleep disturbance play a role in onset as well as in determining natural history. There is an important need for rigorous studies robustly informing the association and mechanism(s) of influence of the external environment on IBD risk and for clinical trials examining the efficacy of alteration of the environment in ameliorating the course of IBD.